PENGARUH TENAGA KERJA, MIGRASI MASUK DAN PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Endang Putri Dewi; Idris Idris (Universitas Negeri Padang, 2019)
This research aims to find out: (1) Influence of Workers on Economic Growth in Indonesian. (2) The Effect of Incoming Migration on Economic Growth in Indonesia (3) Effect of Health Expenditures on Economic Growth in Indonesian (4) Effects of Educational Expenditures on Economic Growth in Indonesian (5) The Influence of Labor, Entry Migration, and Human Development in the field of education and health together Towards Economic Growth in Indonesian. This type of research is descriptive and associative. Data type is secondary data. This study uses panel data which is using 33 provinces in Indonesia using the Common Effect Model (CEM) approach. The results of this study indicate that (1) Labor has a positive and not significant effect on economic growth in Indonesia.(2) Incoming Migration has a negative and not significant effect on Economic Growth in Indonesia (3) Health Expenditures have a negative and not significant effect on Economic Growth in Indonesia(4) Health Expenditures have a negative and not significant effect on Economic Growth in Indonesian.